Relationship of Knowledge with Readiness to Prevent the Occurrence of HIV / AIDS in Aliyah Guppi Students - Edison Siringoringo; Amirullah; Nurlinda (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2018)
One of the viruses that is currently a concern of the world community, because it is considered very dangerous for the survival of a nation is the Human Immunodeficiency Virus (HIV). HIV is a virus that paralyzes the immune system so that it causes Acquired Immune Deficiency Syndrome (AIDS). AIDS stands for Acquired Immune Deficiency Syndrome is a disease characterized by damage to the body's defense system, so that sufferers are easily attacked by a variety of severe infections and unusual cancers. AIDS is caused by the Human Immunodeficiency Virus (HIV). The research design used in this study was observational analytic that is examining the relationship between variables. With a cross-sectional study approach. The population of all students of Madrasah aliyah guppi gunung Jati. The sampling method in this study uses the Nonprobability Sampling method with the sampling technique was purposive sampling with a total of 48 samples based on the sampling formula from Isaac and Michael. Knowledge about HIV / AIDS from 48 respondents can be seen that the most on good knowledge are as many as 47 (97.9%) respondents. Readiness to prevent the occurrence of HIV / AIDS is the most ready to prevent as many as 45 (93.8%) respondents. There is no relationship of knowledge with readiness to prevent the occurrence of HIV / AIDS from the proposed hypothesis known p of 1,000, when compared with an α value of 0, 05 (1,000> 0.05).